Risk factors for low high-density lipoprotein among Asian Indians in the United States - Lucke-Wold, Brandon (World J Diabetes, 2017)
AIM: To examine the differences in metabolic risk factors (RFs) by gender in the Asian Indian (AI) population in the United States. METHODS: Using cross-sectional data from 1038 randomly selected Asian Indians, we investigated the relationship between metabolic syndrome (MetS) RFs, cardiovascular disease, and diabetes. RESULTS: A greater percent of women in this group had increased waist circumference and low high density lipoprotein (HDL) levels than men, but AI males had increased blood glucose, increased blood pressure, and increased triglycerides compared to females. Those individuals who met the MetS criteria had increased cardiovascular disease. One of the biggest single RFs for cardiovascular disease and diabetes reported in the literature for AIs is low HDL. CONCLUSION: Our results show that lack of knowledge about diabetes, low physical activity, increased body mass index, and age were the factors most significantly correlated with low HDL in this population. Future studies and prospective trials are needed to further elucidate causes of the MetS and diabetes in AIs.